Imaging skeletal trauma - Rogers, Lee F. 1934-; West, O. Clark (Saunders, an imprint of Elsevier Inc., 2015)
Imaging of Skeletal Trauma continues to offer a comprehensive view of diagnostic imaging in the evaluation of skeletal trauma